Applied Artificial Intelligence, Big Data Adoption/Avoidance in Public Relations: A Proposed Applied Optimal Macroeconomic Policy Model and Examination - Hamzaee, Reza G; Salimi, Maryam (Archives of Business Research, 2023)
The advantages and critical challenges of Artificial Intelligence (AI) in cost savings, extreme speed, accuracy, and machine learning to take over some human’s less precise performances, all and all, have come into some pronounced stressful and reasonable ambitions as well as fears of the conflicts with the potential as well as some actual damages that AI has imposed and can further impose on society in an enormous number of major events of our lives. Both the topic and the corresponding controversies are appalling. The authors analyze AI through its implications and their own developed applied VAR theoretical model in economic policy and public relations, where massive data are possible to be compiled, labeled, and categorized into segments, and inserted into their proposed VAR econometric model, and Impulse Response Functions, rendering some statistically significant results.